Anatomy of highjump from intra- and intermuscular models - Bosch, F. (3rd European Pole Vault Conference - Köln 2008, 2008)
Author examines the anatomy of highjump from intra- and intermuscular models. Conclusion: High jump is reflex based. When high jump is reflex based, also training should be reflex based (incl. strength training). Because reflexes are very stable patterns, it is possible to make precise rules for optimal high jump technique P-step should be directed upward. Vertical direction of GRF should be focus in training.